Face Masks Use to Avoid Airborne Contamination during COVID-19 Pandemic and Related Conditions: A Systematic Review - Danúbia Cunha Sá-Caputo; Ana Carolina Coelho-Oliveira; Anelise Sonza; Laisa Liane Paineiras-Domingos; Redha Taiar; Satya Das; Alexandre Ribeiro Bello; Mario Bernardo-Filho (Tehran University of Medical Sciences, 2021)
Background: The facemasks use has been discussed to prevent respiratory disease due airborne contamination. The aim of this study was to perform a systematic review about the face masks use to avoid airborne contamination during COVID-19 pandemic and related conditions, registered (PROSPERO-CRD42020198347) and performed according PRISMA. Methods: PubMed, Embase and Scopus databases were used to collect data. Observational studies, published in 2020, and English language, were included. Two reviewers independently identified records through database search and reference screening and disagreements were resolved by a third reviewer. Six studies were included. Results: The works investigated about the use of masks (different types) to prevent droplets dissemination with virus or bacterial suspension and decrease COVID-19 transmission routes, comfort, or temperature. The studies have moderate to critical risk of bias and the level of evidence is III-2. Conclusion: It is recommended facemask use to prevent droplets from escaping airborne and infecting other people, although there are different percentages of protection and can be possible a discomfort related the use. Further clinical trials to the effectiveness of face mask to avoid airborne contamination during the COVID-19 pandemic and the factors interfering with their effectiveness should be conducted.